2010
DOI: 10.1142/s0218127410025739
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Symmetry Breaking and First-Order Phase Transitions of Adsorbed Fluids

Abstract: A density functional formalism is applied to investigate the wetting behavior of Ne confined in slits composed of two parallel solid identical alkaline walls with increasing attractive strength leading to a variety of wetting situations. The study is performed over the complete range of temperature spanned from the triple point T t up to the critical one T c of Ne. Attention is paid to the slit's width. It was found that in the case of weaker substrates for temperatures below a certain critical T sb the densit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
4

Relationship

4
0

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…They found asymmetric solutions with lower free energies than that of corresponding symmetric ones in certain ranges of coverage which shrink for increasing temperatures and disappear at a critical temperature T ssb . Subsequent studies of the filling of this kind of slits with classical gases confirm that behavior. Furthermore, Berim and Ruckenstein reported asymmetric profiles for quantum 4 He confined in closed symmetric planar slits of Cs.…”
Section: Introductionmentioning
confidence: 73%
See 1 more Smart Citation
“…They found asymmetric solutions with lower free energies than that of corresponding symmetric ones in certain ranges of coverage which shrink for increasing temperatures and disappear at a critical temperature T ssb . Subsequent studies of the filling of this kind of slits with classical gases confirm that behavior. Furthermore, Berim and Ruckenstein reported asymmetric profiles for quantum 4 He confined in closed symmetric planar slits of Cs.…”
Section: Introductionmentioning
confidence: 73%
“…The present calculations have been carried out in the frame of the DF theory recently applied for studying physical adsorption of Ne and Ar. ,, This theory is based on the existence of a grand canonical functional Ω( T , μ, [ρ( r )]) of the one-particle density ρ( r ), which depends parametrically on the two thermodynamic variables T and μ normalΩ ( T , μ , false[ ρ ( r ) false] ) = F DF ( T , false[ ρ ( r ) false] ) μ N where F DF is the DF for the Helmholtz free energy and N the number of adatoms N = prefix∫ ρ false( boldr false) d r The equilibrium density profile ρ eq ( r ) of the adsorbed fluid is obtained by solving the Euler–Lagrange (E–L) equation derived by minimizing (at fixed T and μ) the grand thermodynamic potential δ normalΩ ( T , μ , false[ ρ false] ) δ ρ ( r ) | ρ = ρ eq ( r ) = 0 The value of the functional at equilibrium, Ω( T , μ, [ρ = ρ eq ]), is the real equilibrium grand canonical free energy Ω eq .…”
Section: Theoretical Framementioning
confidence: 99%
“…However, it was found that inert gases adsorbed on alkali metals exhibit SSB. Results for Ne confined by such substrates were recently reported [8].…”
Section: Introductionmentioning
confidence: 87%
“…Preliminary results for Ne and Ar confined in such a type of slits have recently been reported elsewhere. 14,15 In the present work we shall report on a rather comprehensive investigation about the behavior of Ar confined in slits of two identical planar walls. The calculations have been carried out within the density functional ͑DF͒ theory.…”
Section: Introductionmentioning
confidence: 99%